FAKTOR YANG MEMPENGARUHI ERC PADA PERUSAHAAN MANUFAKTUR INDONESIA YANG TERDAFTAR DI BEI - Brigitta Patricia Pandana, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This research is purposely done to analyze the effect of firm size, dividend payout ratio, profitability, and leverage on Earnings Response Coefficient (ERC). This research used 90 samples of manufacturing enterprises which is listed on the Indonesia Stock Exchange from the period of 2016-2018. The data in this research was processed using the multiple regression analysis from E-Views 9.0. Based on the analysis, it could be concluded that firm size and leverage have a significant effect on ERC. In the meanwhile, dividend payout ratio and profitability don’t have a significant effect on ERC. Firm size, dividend payout ratio, profitability, and leverage simultaneously have a significant effect on ERC.